Janus kinase inhibitors - their current applications and future prospects - Natalia Wierzbowska; Karolina Żurawska; Maciej Arciszewski; Arnold Kukowka; Bolesław Banach (Farmacja Polska, 2022)
Janus kinase inhibitors are a group of drugs that provide an alternative to conventional therapy for numerous diseases. The most studied drug of this group is tofacitinib. They are used in cases of inadequate response to treatment, intolerance of first-line drugs or presence of severe side effects resulting from taking other medications for a specific disease. At present, Janus kinase inhibitors are used in medical fields such as rheumatology, gastroenterology, hematooncology and dermatology. On the other hand, they are being tested in many other branches of medicine, e.g. in infectious diseases (mainly in SARS-COV-2 virus infection). Janus kinases are receptor-associated proteins. They are responsible for the activation of STAT proteins, which are responsible for transmitting signals directly to the cell nucleus, where they influence the expression of proteins. Thus, the janus kinase inhibitors are affecting the intracellular signaling pathway. Their inhibition of the JAK/STAT signaling pathway provides numerous opportunities to modulate pathways leading to specific body responses, such as reducing inflammatory responses. This fact contributes to the use of Janus kinase inhibitors in pharmacotherapy of numerous autoimmune diseases such as psoriasis and rheumatoid arthritis. Like most drugs, Janus kinase inhibitors have their side effects. These are mainly due to their selectivity for several kinases simultaneously. The situation is different for second-generation inhibitors, which are much more selective towards inhibition of a specific JAK/STAT pathway, and thus their use is associated with a lower risk of adverse side effects. More data is needed to fully comprehend the potential of janus kinase inhibitors. Currently, numerous studies on Janus kinase inhibitors are being conducted in order to: test their safety, extend their therapeutic range, create new Janus kinase inhibitors, and investigate the benefits of using Janus kinase inhibitors together with previously used drugs in combination therapy.